LRSAM1-mediated ubiquitylation is disrupted in axonal Charcot–Marie–Tooth disease 2P. (15th March 2017) - Hakonen, Johanna E.; Sorrentino, Vincenzo; Avagliano Trezza, Rossella; de Wissel, Marit B.; van den Berg, Marlene; Bleijlevens, Boris; van Ruissen, Fred; Distel, Ben; Baas, Frank; Zelcer, Noam; Weterman, Marian A.J.
Abstract: Charcot–Marie–Tooth (CMT) disease type 2 is a genetically heterogeneous group of inherited neuropathies characterized by motor and sensory deficits as a result of peripheral axonal degeneration. We recently reported a frameshift (FS) mutation in the Really Interesting New Gene finger (RING) domain of LRSAM1 (c.2121_2122dup, p.Leu708Argfs) that encodes an E3 ubiquitin ligase, as the cause of axonal-type CMT (CMT2P). However, the frequency of LRSAM1 mutations in CMT2 and the functional basis for their association with disease remains unknown. In this study, we evaluated LRSAM1 mutations in two large Dutch cohorts. In the first cohort ( n = 107), we sequenced the full LRSAM1 coding exons in an unbiased fashion, and, in the second cohort ( n = 468), we specifically sequenced the last, RING-encoding exon in individuals where other CMT-associated genes had been ruled out. We identified a novel LRSAM1 missense mutation (c.2120C > T, p.Pro707Leu) mapping to the RING domain. Based on our genetic analysis, the occurrence of pathogenic LRSAM1 mutations is estimated to be rare. Functional characterization of the FS, the identified missense mutation, as well as of another recently reported pathogenic missense mutation (c.2081G > A, p.Cys694Tyr), revealed that in vitro ubiquitylation activity was largely abrogated. We demonstrate that loss of the E2–E3 interaction that is an essential prerequisite for supporting ubiquitylation of target substrates, underlies this reduced ubiquitylation capacity. In contrast, LRSAM1 dimerization and interaction with the bona fide target TSG101 were not disrupted. In conclusion, our study provides further support for the role of LRSAM1 in CMT and identifies LRSAM1-mediated ubiquitylation as a common determinant of disease-associated LRSAM1 mutations.